Workplace bullying and workplace violence as risk factors for cardiovascular disease: a multi-cohort study - Xu T; Magnusson Hanson LL; Lange T; Starkopf L; Westerlund H; Madsen IEH; Rugulies R; Pentti J; Stenholm S; Vahtera J; Hansen ÅM; Virtanen M; et al. (United Kingdom, 2022)
Aims To assess the associations between bullying and violence at work and cardiovascular disease (CVD).
Methods and results Participants were 79 201 working men and women, aged 18–65 years and free of CVD and were sourced from three cohort studies from Sweden and Denmark. Exposure to workplace bullying and violence was measured at baseline using self-reports. Participants were linked to nationwide health and death registers to ascertain incident CVD, including coronary heart disease and cerebrovascular disease. Study-specific results were estimated by marginal structural Cox regression and were combined using fixed-effect meta-analysis. Nine percent reported being bullied at work and 13% recorded exposure to workplace violence during the past year. We recorded 3229 incident CVD cases with a mean follow-up of 12.4 years (765 in the first 4 years). After adjustment for age, sex, country of birth, marital status, and educational level, being bullied at work vs. not was associated with a hazard ratio (HR) of 1.59 [95% confidence interval (CI) 1.28–1.98] for CVD. Experiencing workplace violence vs. not was associated with a HR of 1.25 (95% CI 1.12–1.40) for CVD. The population attributable risk was 5.0% for workplace bullying and 3.1% for workplace violence. The excess risk remained similar in analyses with different follow-up lengths, cardiovascular risk stratifications, and after additional adjustments. Dose–response relations were observed for both workplace bullying and violence (Ptrend < 0.001). There was only negligible heterogeneity in study-specific estimates.
Conclusion Bullying and violence are common at workplaces and those exposed to these stressors are at higher risk of CVD.